Alat Pengusang Cepat IPB 77-1 MM untuk Penapisan Vigor Daya Simpan Benih Kedelai - Terryana, Rerenstradika Tizar; Suhartanto, M. R.; Qadir, Abdul (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Accelerated Aging Machine â€œIPB 77-1 MMâ€ could be used for soybean seed screening based on the seed storability vigor. The aim of the research was to identify simple, fast and accurate accelerated aging method using accelerated aging machine IPB 77-1 MM. Two methods of accelerated aging test (physical and chemical treatment) were applied to seeds of Anjasmoro soybean variety. The best accelerated aging method was then used to screen seed storability vigor of 23 soybean varieties. Seed storability vigor of 23 soybean varieties were detected using accelerated aging machine IPB 77-1 MM and each was compared with the seed storability vigor of those stored 10 weeks in controlled storage. Results of the experiment showed that using chemical or physical treatment on accelerated aging process were able to decrease seed vigor, but chemical treatment decreased seed vigor faster, more simple and more practical. Accelerated aging machine IPB 77-1 MM could also be used for screening varietal seed storability vigor of soybean using electrical conductivity test.